Cocalero (2006) d’Alejandro Landes, un documentaire « historique » sur l’élection d’Evo Morales - Emmanuel Larraz (Caravelle)
This article tries to demonstrate the importance of the documentary Cocalero (2006) by Alejandro Landes, based upon the thesis of the indirect responsibility of United States of America’s, and specially DEA, interventionist politics which permitted the historical accession of a Native to the presidency in Bolivia. It shows the strength of the coca farmers’ trade unions, the cocaleros, and draws a balanced but nevertheless a very favourable picture of their leader Evo Morales, drawing attention to his simplicity, humour and moral sense.